Mapping and Assessing Green Infrastructure Connectivity in European City Regions. - Rusche, Karsten; Reimer, Mario; Stichmann, Rico (MDPI, 2019)
Urban green infrastructure is becoming an increasingly important concept for sustainable urban planning. In the past, planning practice and research have worked on defining principles and suggesting relevant indicators to promote the concept. While there has been a focus on multifunctionality of green infrastructure elements, the connectivity principle is underrepresented, especially in urban research. Therefore, this paper suggests land use indicators to map and assess the degree of connectivity of open spaces within the urban realm. Empirical results are presented for three European case studies. The relevance of connectivity indicators for urban green infrastructure planning is highlighted and linked to future needs for improving strategic urban planning.
Keywords: Freiraumplanung; Stadtplanung; Flächennutzung; Nachhaltige Entwicklung; Stadtraum; Räumliche Verteilung; Stadtgrün; Grünplanung; Landschaftsplanung; Grüne Infrastruktur